FDG PET in the differential diagnosis of degenerative parkinsonian disorders: usefulness of voxel-based analysis in clinical practice - Arnone, Annachiara; Allocca, Michela; Di Dato, Rossella; Puccini, Giulia; Laghai, Iashar; Rubino, Federica; Nerattini, Matilde; Ramat, Silvia; Lombardi, Gemma; Ferrari, Camilla; Bessi, Valentina; Sorbi, Sandro; et al. (Neurological sciences, 2022)
Background The early differential diagnosis among neurodegenerative parkinsonian disorders becomes essential to set up the correct clinical-therapeutic approach. The increased utilization of [ 18 F] fluoro-deoxy-glucose positron emission tomography (FDG PET) and the pressure for cost-effectiveness request a systematic evaluation and a validation of its utility in clinical practice. This retrospective study aims to consider the contribution, in terms of increasing accuracy and increasing diagnostic confidence, of voxel-based FDG PET analyses in the differential diagnosis of these disorders, including Parkinson’s disease, multiple system atrophy, progressive supranuclear palsy, and cortico-basal syndrome. Method Eighty-three subjects with a clinically confirmed diagnosis of degenerative parkinsonian disorders who underwent FDG brain PET/CT were selected. A voxel-based analysis was set up using statistical parametric mapping (SPM) on MATLAB to produce maps of brain hypometabolism and relative hypermetabolism. Four nuclear physicians (two expert and two not expert), blinded to the patients’ symptoms, other physicians’ evaluations, and final clinical diagnosis, independently evaluated all data by visual assessment and by adopting metabolic maps. Results In not-expert evaluators, the support of both hypometabolism and hypermetabolism maps results in a significant increase in diagnostic accuracy as well as clinical confidence. In expert evaluators, the increase in accuracy and in diagnostic confidence is mainly supported by hypometabolism maps alone. Conclusions In this study, we demonstrated the additional value of combining voxel-based analyses with qualitative assessment of brain PET images. Moreover, maps of relative hypermetabolism can also make their contribution in clinical practice, particularly for less experienced evaluators.